2016
DOI: 10.5812/archcid.33343
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Producing Staphylococcus epidermidis Strains Isolated From Clinical Samples in Tehran, Iran

Abstract: Background: Staphylococcus epidermidis is well documented as an opportunistic pathogen causing biofilm in patients and healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Observed results happen to be the same as Delpozo and Patel Filho's findings [8,17]. In 2016, two different studies investigated clinical isolates of S. epidermidis collected from a private hospital in Tehran [18] and clinical isolates from Shiraz city [19]. Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Observed results happen to be the same as Delpozo and Patel Filho's findings [8,17]. In 2016, two different studies investigated clinical isolates of S. epidermidis collected from a private hospital in Tehran [18] and clinical isolates from Shiraz city [19]. Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19].…”
Section: Discussionsupporting
confidence: 74%
“…Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19]. Rahimi reported that 82% of the isolated strains were biofilm-formers and all of the biofilm former S. epidermidis isolates carried icaA, icaD, aap, and atlE genes [18]. Granting to the previous findings, [20] sdrG and certain genes have a crucial role in biofilm formation of clinically isolated strains.…”
Section: Discussionmentioning
confidence: 70%
“…Using a high-quality PFGE typing method, we found the presence of certain clonal groups of MRSE in patients with UTI at a referral hospital in Tehran, Iran. The MRSE strains in this study had the lowest frequency among hospitalized patients in Iran (12,20) that could be partly due to the fact that in this study, we focused on isolating MRSE strains from UTI patients with indwelling medical devices. The combination of two different quantitative and qualitative biofilm assays revealed that 89% of the MRSE strains were slime producers.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, CTs 2 -4 and CT 6 were common among biofilm and non-biofilm producing isolates and none of the biofilm producing strains were present in CT 9. IS256 was found among all strains in 6 CTs (3,7,10,(12)(13)(14) while none of the strains in CTs 5 and 9 harbored this transposon.…”
Section: Typing Of Isolates By Pulsed-field Gel Electrophoresismentioning
confidence: 91%
See 1 more Smart Citation